IBM UNTUK PETANI SAYUR PENGOLAHAN KRIPIK TERONG DAN WORTEL DI DESA LANJAN KECAMATAN SUMOWONO KABUPATEN SEMARANG - Sucihatiningsih DWP; Asih Kuswardinah; Fafurida Fafurida (Rekayasa)
Agriculture-based business development efforts is crucial carried out in support of public welfare. One of the agricultural products which have the potential to be developed towards an industrial scale are fruits and vegetables. During this time, farmers only sell fruit and vegetables in the form of raw products, and product diversification are less in touch. So far, farmers also simply be a price taker, where they do not have the strength in pricing. This causes farmers sometimes manipulated by middlemen, especially when the harvest is abundant. Therefore, it takes effort and innovation to cultivate fruit and vegetables to be more durable, has a high economic value and improve the welfare of farmers. The purpose of this service is: (1) provide training on making chips eggplants and carrots; (2) facilitate the use of freezingfrying machines; (3) help the vegetable farmers in assessing the feasibility of making chips eggplants and carrots (4) facilitate and assist farmers in accessing capital loans to financial institutions (5) business assistance. The methods used in service activities are 1) a method of action which the servants of training the production of chips eggplant and vegetables, 2) methods of assistance where efforts procurement of machines, access to capital and feasibility studies done here and, 3) the method of supervision, which in the method The servant evaluate and solve problems encountered while running a business. After the service is implemented, is expected to solve the existing problems so as to support the promotion of the local economy and local vegetable growers.